2022
DOI: 10.3390/cancers15010176
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomic Profiles of Lung Pre-Metastatic Niche Reveal Neutrophil and Lymphatic Endothelial Cell Roles in Breast Cancer

Abstract: The establishment of a pre-metastatic niche (PMN) is critical for cancer metastasis. However, it remains unclear as to which phenotypes induce changes in the PMN. Single-cell transcriptomic profiling of all cells of the lung in cancer-bearing MMTV-PyVT mice revealed an increased infiltration of N2-type neutrophils and classical monocytes associated with chronic inflammation; notably, lung neutrophils isolated from mice with primary cancer exhibited similar N2-type phenotypes and expressed high levels of inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Notably, CD11b+Ly6G+ immune cells are reported to inhibit CD8+ T cell functions and facilitate breast cancer metastasis 42 . Neutrophils also play a critical role in creating a pre-metastatic niche in the lung microenvironment and their reduction may contribute to a potentially less permissive environment for metastatic seeding and colonization in breast cancer 45,46 . The alterations in immune cell infiltrates, such as increased CD8+ T cells, B cells with reduced PD-L1 expression, and decreased neutrophils suggest that iEF treatment hinders metastasis by orchestrating changes in the immune landscape of the lung microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, CD11b+Ly6G+ immune cells are reported to inhibit CD8+ T cell functions and facilitate breast cancer metastasis 42 . Neutrophils also play a critical role in creating a pre-metastatic niche in the lung microenvironment and their reduction may contribute to a potentially less permissive environment for metastatic seeding and colonization in breast cancer 45,46 . The alterations in immune cell infiltrates, such as increased CD8+ T cells, B cells with reduced PD-L1 expression, and decreased neutrophils suggest that iEF treatment hinders metastasis by orchestrating changes in the immune landscape of the lung microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to the recruitment of neutrophils with high levels of C3a receptors to pre-metastatic niche, supporting metastasis [ 34 ]. Huang et al identified a group of lymphatic endothelial cells (EC) with increased Ki67 and S100A6 expression,which impaired EC tight junction and increased the transendothelial migration of neutrophils [ 35 ].…”
Section: Neutrophil Chemotaxis Towards Pre-metastatic Nichementioning
confidence: 99%